2007
DOI: 10.1186/1475-2859-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundRecombinant proteins expressed in Escherichia coli vectors are generally contaminated with endotoxin. In this study, we evaluated the ability of Polymyxin B to neutralize the effect of LPS present as contaminant on Schistosoma mansoni recombinant proteins produced in E. coli in inducing TNF-α and IL-10. Peripheral blood mononuclear cells from individuals chronically infected with S. mansoni were stimulated in vitro with recombinant Sm22.6, Sm14 and P24 antigens (10 μg/mL) in the presence of Polymyxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(85 citation statements)
references
References 16 publications
(20 reference statements)
1
83
1
Order By: Relevance
“…Although the specific role that Alg44 plays in polymerization remains unclear, Alg44 could play an indirect role. It has been suggested that there is a mutual stability relationship between Alg8 and Alg44 [3]. The findings obtained in our study, which indicate that the expression of alg8 and alg44 was not related to higher alginate MMW (obtained at 500 rpm), could be explained by a mutual stability relationship between Alg8 and Alg44.…”
Section: Resultscontrasting
confidence: 53%
“…Although the specific role that Alg44 plays in polymerization remains unclear, Alg44 could play an indirect role. It has been suggested that there is a mutual stability relationship between Alg8 and Alg44 [3]. The findings obtained in our study, which indicate that the expression of alg8 and alg44 was not related to higher alginate MMW (obtained at 500 rpm), could be explained by a mutual stability relationship between Alg8 and Alg44.…”
Section: Resultscontrasting
confidence: 53%
“…In order to neutralize the potential effects of lipopolysaccharide found in low levels in Schistosoma- recombinant antigens, polymyxin B was added to cell cultures every 12 h according to an established protocol [14]. …”
Section: Methodsologymentioning
confidence: 99%
“…High-temperature-active or -stable enzymes are more favorable than mesophilic counterparts, since high temperatures enhance the mass transfer rate, reduce the substrate viscosity, and reduce the risk of contamination (8,9). For example, thermophilic xylanases are applied in bioconversion processes and pulp bleaching, during which a variety of high-temperature treatments are used prior to or simultaneously with enzyme treatment.…”
mentioning
confidence: 99%